RAG1 and ITS2 GenBank accession numbers: MF555591-MF555594 - Walter, Ryan P.; Roy, Denis; Hussey, Nigel E.; Stelbrink, Björn; Kovacs, Kit M.; Lydersen, Christian; McMeans, Bailey C.; Svavarsson, Jörundur; Kessel, Steven T.; Porsmoguer, Sebastian Biton; Wildes, Sharon; Tribuzio, Cindy A.; et al. (Dryad Digital Repository, 2017)
GenBank Accession numbers for partial nuclear sequences for the RAG1 locus, and ITS2 locus with flanking 5.8S and 28S regions associated with Somniosus microcephalus and Somniosus pacificus.